Implementation Of Urban Community Empowerment Program In Gebang Putih Sub-District, Sukolilo District Surabaya Community - Setyadarma, Bambang; Poernomo, Tri Tjahjo; Putri, Husni Indrawati Wijaya (International Journal of Social and Management Studies, 2023)
Implementation of accountability for the progress of the revolving of community self-help program funds (repair of uninhabitable houses), can run well during the period May 1 to June 30 2022, the whole community in Gebang Putih Village, Sukolilo District, Surabaya can reap the economic benefits along with increasing aspects of impact social. In order to enjoy decent housing on an ongoing basis through the management of the Gebang Barokah community self-help agency (multi-year program), especially a group of people in the Gebang Putih Village, Sukolilo District, Surabaya, today. The target location of the activity includes the administrative area of the government of Gebang Putih Village, Sukolilo District, Municipality of Surabaya (East Java Province). The functional goal is to accommodate and realize the entire implementation of program activities, starting from planning, implementation in the field and results along with the obstacles encountered during the implementation of program activities. The operational goal is the clear implementation of all activities, which include program actors, program targets (low-income people in quantity) and targets to be achieved as well as support for national programs/movements in order to realize the provision of clean and comfortable social environmental infrastructure sanitation in accordance with the proposed concept village investment program (KIP)-based environmental development independently with national integration.